Functional status in a teenager with phenylketonuria from the ICF perspective - Bingöl Hasan; Günel, M. K. (Georg Thieme Verlag, 2017)
Objective The case aims to present a teenager with phenylketonuria in terms of functional status, by using theWorld Health Organization's International Classification of Functioning, Disability, and Health (ICF) perspective. Case Description A 17-year-old teenager with phenylketonuria, classified level V in accordance with the Functional Mobility Scale, was recruited in this study. To exhibit body structure, functional status, participation, activity, and environmental and individual factors, assessment tools classified according to ICF for Children and Youth major categories were implemented. Result After the assessment tools were applied, we found various problems ranging from body structure, function, and activity, to participation. In addition to these problems, there were cognitive problems as well. Conclusion Despite various physical problems, the teenager suffered from cognitive problems more, that is, compared with physical problems in the teenager with phenylketonuria, cognitive problems constituted a bigger barrier to participation in daily life. © 2017 Georg Thieme Verlag KG Stuttgart.
Keywords: activity; functional status; ICF; participation; phenylketonuria